Characterisation and performance of three Kenaf coagulation products under different operating conditions - Okoro, Benjamin U.; Sharifi, Soroosh; Jesson, Mike; Bridgeman, John; Moruzzi, Rodrigo [UNESP] (Elsevier, 2021)
The Sustainable Development Goal (SDG) 6.1, established by the United Nations General Assembly in 2015, targets universal and equitable access to safe and affordable drinking water for all by 2030. An essential factor in achieving this goal is the harnessing of “green” coagulants – naturally occurring, environmentally friendly materials which are effective coagulants for use in water treatment, with good availability in developing countries, inherent renewable properties and ease of biodegradation. In order to gain from these benefits, it is essential to fully understand how such coagulants may best be utilised, particularly concerning their practical application in developing countries. In this study, three different plant-based coagulation products (PCPs), namely Hexane (HxKP), saline (StKP) and crude (CrKP) extracts of Kenaf plant seed (Hibiscus cannabinus, a species of the Hibiscus plant), were applied to high (HTW), medium (MTW) and low (LTW) turbidity water in order to determine their performance and coagulation ability. The ability of the three Kenaf coagulant products (KCPs) to remove hydrophobic fractions of natural organic matter (NOM) was measured. The impact of KCPs on the treated water organic matter content (a known disinfection by-product (DBP) precursor) was examined using known surrogates of natural organic matter (NOM) i.e. the dissolved organic carbon (DOC), ultraviolet absorbance at 254 (UV254) and specific ultraviolet absorbance (SUVA254). Results obtained quantify the implications of using these coagulants during the water disinfection process. A parametric study, measuring the effect of different operating parameters, such as untreated water turbidity, pH, dosages, retention time, and KCP storage time, was completed. Turbidity removal performance for HxKP and StKP was very good with > 90% removal recorded for HTW and MTW, respectively, at pH seven within 2 hours retention time. Images obtained from scanning electron microscopy (SEM) analysis revealed a high likelihood of the coagulation mechanism of KCPs to be adsorption-interparticle bridging brought about by their flake-like structures and surfaces charges. Varying pH had no measurable influence on the coagulation performance of the KCPs. Comparing their efficiency with MoringaOleifera (MO, a previously researched PCP) and alum showed that HxKP had a negligibly different particle removal as MO. StKP turbidity removal performance was below HxKP by 1% for HTW and LTW and 2% for MTW but performed higher than the CrKP by 5% and 7% in HTW and MTW, respectively. The optimum dosage of HxKP and StKP reduced DBP surrogate values, indicating that its precursor is also minimized, although a slight shift from this optimum dosage showed a significant rise in their concentration thus signifying a potential increase in DBPs during disinfection.
Keywords: Coagulation-flocculation; Molecular interaction; Plant-based coagulants; Turbidity; Water treatment